INDONESIAN EFL TEACHERS ENGAGEMENT IN CLASSROOM ACTION RESEARCH - Mukrim; Hastini (Journal of Islamic, Social, Economics and Development, 2023)
This study aims to investigate English as Foreign Language (EFL) teachers’ engagement in Classroom Action Research (CAR) with an emphasis on defining levels of teacher involvement, benefits gained in CAR engagements and the main challenges which inhibit practicing CAR. 54 teachers from several Junior Secondary Schools in Palu participated in this mixed-method study by filling out an online questionaire survey, followed by two Zoom-meeting interviews with 11 of the participating teachers. The present study found that the teachers have engaged in CAR, and some others never practise it due to personal and contextual challenges. Additionally, CAR helps teachers to reflect on their practices, develops their knowledge and skills about research and CAR report writing, and improves pedagogical practices. However, considerable challenges were encountered by teachers which apparently subdued their motivation to continue engaging in CAR projects. Teachers’ workload had been identified as the main challenge, compounded with limited knowledge of doing CAR and writing its report, lack of incentive support and collaborators, and limited school facilities. The study implication to all-stakeholders of teacher professional development is discussed.